Development and optimization of an integrated PDMS based‐microdialysis microchip electrophoresis device with on‐chip derivatization for continuous monitoring of primary amines. Issue 6 (26th February 2013) - Nandi, Pradyot; Scott, David E.; Desai, Dhara; Lunte, Susan M.
<x xml:space="preserve">Abstract</x> An all‐PDMS on‐line microdialysis‐microchip electrophoresis with on‐chip derivatization and electrophoretic separation for near real‐time monitoring of primary amine‐containing analytes is described. Each part of the chip was optimized separately, and the effect of each of the components on temporal resolution, lag time, and separation efficiency of the device was determined. Aspartate and glutamate were employed as test analytes. Derivatization was accomplished with naphthalene‐2, 3, ‐dicarboxyaldehyde/cyanide (NDA/CN−), and the separation was performed using a 15‐cm serpentine channel. The analytes were detected using LIF detection.